Cambarus (Jugicambarus) adustus, a new species of crayfish from northeastern Kentucky delimited from the Cambarus (J.) aff. dubius species complex - Thoma, Roger F.; Fetzner, James W. Jr.; Stocker, G. Whitney; Loughman, Zachary J. (Zootaxa, 2016)
A new species of burrowing crayfish, Cambarus (Jugicambarus) adustus, is described from Lewis County in northeastern Kentucky, USA. The new species is most similar morphologically to C. dubius. Cambarus adustus coloration differs from C. dubius by lacking red, orange and blue hues, and instead is brown over the entire body surface. Morphological differences between C. dubius and C. adustus exist in the form I male gonopod, with C. adustus possessing a caudal knob, while C. dubius does not. In addition, the lateral carapace of C. adustus is distinctly tuberculate, whereas in C. dubius the carapace lacks extensive tuberculation. Cambarus (J.) adustus appears to have an extremely small geographic range ( 19.5 km2), and as such we suggest its consideration for both state and federal levels of protection.